Introduction to Food Chemistry Compiled by Okewole, Samson Ademola, Aribisala, Lukman Aderemi, Akande, Oluwaseun Olusola, and Olugbodi, Olumide Gbenga - Ademola , Okewole Samson; Aderemi , Aribisala Lukman; Olusola , Akande Oluwaseun; Gbenga, Olugbodi Olumide (Current Perspectives in Agriculture and Food Science Vol. 8, 2024)
Food chemistry is a major aspect of food science that deals with the composition and properties of food and the chemical changes it undergoes during handling, processing, and storage. This chapter of the book defines food and food technology, gives adequate information on the origin of food, and technology involved in processing food into consumable product. Food origins are classified into two; plant and animal origin, examples and nutrient supply were given. The technology involved in processing these food sources to achieve the intended changes was discussed. It also gives practice questions for self-assessment which are made available at the end of the chapter.